Determination of Aflatoxin M1 levels in Turkish cheeses provided from different regions of Turkey - Ergin, SÖ; Çakmak, Ö; Çakmak, T; Acaröz, U; Yalçın, H; Acaröz, DA; İnce, S (Journal of the Hellenic Veterinary Medical Society, 2023)
Hygienic quality is a very important problem in milk and dairy products. Aflatoxins are produced by moulds, and it is known that the Aflatoxin M1 type, which can be found in milk and dairy products, is a potential risk for public health. In this study, the presence of Aflatoxin M1 in white and Tulum cheese samples collected from three different provinces of Turkey (Burdur, Bursa, and Elazig) was investigated with the ELISA method. 42 white and 42 Tulum cheese samples (total 84) were analyzed, and the samples were evaluated in terms of their compliance with the limits of the Turkish Food Codex. According to the results; 34 (40.47 %) of 84 cheese samples were contaminated with Aflatoxin M1, ranging from 250 to 559 ng/kg. Fifty (59.52 %) cheese samples were found below the detection limit, meaning they are negative in terms of Aflatoxin M1 and do not pose a risk. On the other hand, 2 samples (2.38 %) were over the tolerance limit of the Turkish Food Codex. Also, the incidence of Aflatoxin M1 in white cheeses was 35.71 % and 45.23 % in Tulum cheeses. Although it is not much above the legal limit, Aflatoxin M1 contamination in cheese may reduce the food quality and adversely affect human health. Therefore, it should be treated more carefully in the production of milk and dairy products. In addition, quality feeds should be used in the feeding of dairy animals.